Uji Efektivitas Antibakteri Ekstrak Metanol Daun Bandotan (Ageratum conyzoides L.) Terhadap Staphylococcus Aureus - Lovera Anggraini; Wahyu Margi Sidoretno; Liza Salsabila Rifwan Putri (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Bandotan (Ageratum conyzoides L.) is a wild plant that is better known as a nuisance plant (weed) in gardens and fields. Bandotan (Ageratum conyzoides L.) has traditional properties, namely to treat infectious diseases of the skin such as boils and wounds caused by bacteria. Staphylococcus aureus is a Gram positive bacterium which is a normal flora in humans and can be pathogenic that causes infection. This study aims to determine the antibacterial activity of the methanolic extract of bandotan (Ageratum conyzoides L.) against the growth of Staphylococcus aureus at concentrations of 10%, 20% and 30%. This research is a laboratory experimental study to determine the diameter of antibacterial inhibition. The method used to test the antibacterial activity in this study was the agar diffusion method and chloramphenicol as a positif control. Extraction method is done by maceration method using methanol solvent. The results of the inhibition test with extract concentrations of 10%, 20% and 30% could inhibit the growth of Staphylococcus aureus with the average diameter of the inhibition zones being 7,3 mm, 8,1 mm, 8,9 mm and the positive control chloramphenicol was 29,3 mm. From the results above, it can be concluded that the methanolic extract of Bandotan leaves (Ageratum conyzoides L.) has antibacterial activity against Staphylococcus aureus.